Shared parenting as an interpretation of the best interest of the child in custody disputes : an overview of the practice in Malaysia - Che Soh @ Yusoff, Roslina (American-Eurasian Network for Scientific Information (AENSI), Jordan, 2011)
In most western countries there is now a consensus that shared parenting is the best alternative for children when their parents separate or divorce. Maintaining elationships with both parents after their divorce, by way of a shared parenting arrangement is said to be the best for the child compared to merely providing contact for the child and the non-resident parent by way of a sole custody arrangement. Such an arrangement would minimise conflict between divorced parents and provide a healthy environment for the child to get adjusted to the divorce, therefore diminishing the probable detrimental effects of parental conflict on the child. The best interest of the child would be preserved as the child is able to retain a strong bond with both parents despite the parental separation. The basis of this concept is as stated in the United Nation Convention on Right of Child 1989, which clearly emphasizes on the importance of both parents to be equally responsible for the upbringing of their children. This paper seeks to examine the extent of the laws and the judicial decisions in Malaysia in upholding shared parenting for the best interest of the child in custody disputes after parental divorce. In doing so, it attempts to provide an overview of the current law and the approach of the courts in granting custody orders. The paper also highlight the problems of implementing shared parenting arrangement, particularly in cases involving determination of the religion of the child and domestic violence. For purposes of comparison, it examines the Australian legislation on custody disputes which has undergone a tremendous shift from that of sole custody standard to that of shared parental responsibility. The Australian experience in advocating shared parenting as the primary custody standard for the best interest of the child in custody disputes should assist Malaysia in improving further the current legislation in custody disputes.